2021
DOI: 10.1177/1063293x21991808
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer prediction using an optimal machine learning technique for next generation sequences

Abstract: A wide reach on cancer prediction and detection using Next Generation Sequencing (NGS) by the application of artificial intelligence is highly appreciated in the current scenario of the medical field. Next generation sequences were extracted from NCBI (National Centre for Biotechnology Information) gene repository. Sequences of normal Homo sapiens (Class 1), BRCA1 (Class 2) and BRCA2 (Class 3) were extracted for Machine Learning (ML) purpose. The total volume of datasets extracted for the process were 1580 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The result of other studies confirm the better performance of DT than other similar algorithms in predicting the BC risk (44,45,50,51). Similarly, in this research, different ML algorithms were used to classify the data, and the DT algorithm had a higher efficiency than other algorithms.…”
Section: Discussionsupporting
confidence: 77%
“…The result of other studies confirm the better performance of DT than other similar algorithms in predicting the BC risk (44,45,50,51). Similarly, in this research, different ML algorithms were used to classify the data, and the DT algorithm had a higher efficiency than other algorithms.…”
Section: Discussionsupporting
confidence: 77%
“…While classifying with 12 features, the random forest algorithm achieved a classification accuracy of 74.73% and XGBoost achieved 73.63%. Nine supervised machine learning techniques including boosting algorithms were applied for breast cancer prediction by extracting 10 features from the genetic sequences of Homo sapiens, BRCA1, and BRCA2 [7]. e decision tree algorithm outperformed other models with 94.03% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…They also observed that the accuracies has been increased a lot and has greater potential in classification of signals by frequency domain signals than the time domain signal. Detection of cancer was highly appreciated in the medical filed using Next Generation Sequencing application (Kurian and Jyothi, 2021). In (Vijayakumar et al, 2021), and the author contributes a precision classification technique to classify the breast cancer images using Deep Neural Network.…”
Section: Introductionmentioning
confidence: 99%